The Indonesian Business Competition Law: How the Police Plays a Role? - Paramita Prananingtyas; Hari Sutra Disemadi; Ninik Zakiyah (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: In Indonesia, there are specialized and independent institutions in enforcing business competition law. The institution is the Business Competition Supervisory Commission or KPPU. It is because the suspected of business actors who violate Act No. 5 of 1999 are often uncooperative. In assisting KPPU, the Anti-Monopoly Law mandates the police to enforce business competition law in Indonesia. But, the extent the police’s role in helping the KPPU’s duty became the arising problem that should be discussed.Purpose/Objective Study: This research wants to discuss the role of the police in enforcing business competition law.Design/Methodology/Approach: This research is doctrinal research (normative juridical); an investigation that uses a statutory approach. The legal material referred to in this study focuses on the primary legal content, namely Act No. 5 of 1999 on Prohibition of Monopoly Practices and Unfair Business Competition, or it often called Anti-Monopoly Law, and the Indonesian Criminal Law Code (KUHP).Findings: This research shows that the police have the authority to uphold business competition law. The Anti-Monopoly Law gives power to the police in assisting KPPU. The provisions for the role of the police are contained in Article 36, Article 41 paragraph (3), and Article 44 paragraph (5) of the Anti-Monopoly Act. The role of the police to enforce business competition law begins at the time of the investigation or inspection process if the KPPU requests assistance to present reported parties, witnesses, expert witnesses, and other parties involved in business competition cases.